2018
DOI: 10.1016/j.agrformet.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual variability of Net Ecosystem Productivity for a temperate mixed forest: A predominance of carry-over effects?

Abstract: A B S T R A C TThis study presents twenty years of Net Ecosystem Productivity estimations obtained using eddy covariance in a mixed forest, dominated by beech with sparse conifers, at the Vielsalm station, in the Belgian Ardennes.First the quality and reliability of the data set is discussed. An uncertainty analysis showed that if, on one hand, the site heterogeneity and set-up changes may strongly affect yearly NEP estimates, questioning thus the total carbon budget relevance, on the other hand, robust inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 50 publications
3
29
1
Order By: Relevance
“…This means that both the current climate conditions and the ones of the previous months or years control NEE seasonal cycle in such an ecosystem. These findings confirmed the existence of different ecosystem type-specific memory or lagged effects (Aubinet et al, 2018).…”
supporting
confidence: 76%
See 4 more Smart Citations
“…This means that both the current climate conditions and the ones of the previous months or years control NEE seasonal cycle in such an ecosystem. These findings confirmed the existence of different ecosystem type-specific memory or lagged effects (Aubinet et al, 2018).…”
supporting
confidence: 76%
“…Similarly, evidence with regard to the vegetation and climate's ecological memory effects has been provided. For instance, spring temperature seems to have variable memory effects on subsequent summer and autumn ecosystem productivity (Buermann et al, 2018), while Aubinet et al (2018) found a dependency of the current ecosystem functioning to previous year water limitation. This evidence points at the need to understand the sensitivity of global ecosystems to past-time climate variability and disturbances.…”
Section: Climate and Vegetation Ecological Memory Effects On The Carbmentioning
confidence: 99%
See 3 more Smart Citations